Characterization of SLC26A9 in Patients with CF‐Like Lung Disease. Issue 10 (13th August 2013) - Bakouh, Naziha; Bienvenu, Thierry; Thomas, Annick; Ehrenfeld, Jordi; Liote, Huguette; Roussel, Delphine; Duquesnoy, Philippe; Farman, Nicolette; Viel, Marion; Cherif‐Zahar, Baya; Amselem, Serge; Taam, Rola Abou; et al.
<x xml:space="preserve">Abstract</x> We report the functional characterization of 2 mutations in SLC26A9 evidenced in patients presenting with idiopathic bronchiectasis. p.Arg575Trp and p.Val486Ile decrease SLC26A9‐mediated chloride (Cl‐) current in Xenopus laevis oocytes. Additionally, p.Arg575Trp also prevents SLC26A9‐mediated CFTR activation (see CFTR‐mediated currents in Xenopus Laevis oocytes expressing either CFTR alone or CFTR and SLC26A9‐WT or SLC26A9‐p.Arg575Trp). Further structure‐function analysis led us to propose a site on the SLC26A9‐STAS domain for the CFTR‐SLC26A9 interaction. Such mutations may trigger the pathogenic role of a single CFTR mutation and provide insight into a novel mechanism of Cl‐ transport alteration across the respiratory mucosa, based on functional inhibition of CFTR. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>